ANALISIS TEKNIK PASSING DENGAN METODE PROBLEM BASED LEARNING DALAM PEMBELAJARAN PERMAIN SEPAK BOLA PADA MAHASISWA PJKR B 2023 - Manalu, Nimrot; Talentia, Talentia; Lumban, Friskila Aryanti; Simanjuntak, Batul Daniel; Sipayung, Jeremia William Isiprasa (Universitas Negeri Medan, 2025)
Soccer is a sport that requires team solidity to achieve a good game. This study aims to analyze the application of passing techniques through the Problem Based Learning (PBL) method in learning football for students of the Physical Education, Health and Recreation (PJKR) Study Program class B year 2023 at Medan State University. The research was conducted on Friday, February 18, 2025 at the Medan State University stadium with a qualitative approach. Data collection techniques include cognitive, affective, and psychomotor assessments. The research subjects were 32 PJKR B 2023 students. The results showed that the average student activity was 77.03%, with a learning activity completeness rate of 79%. The conclusion of this study shows that the application of the PBL method is able to increase learning activities and understanding of passing techniques in soccer, and encourage active participation of students in the learning process.